2017
DOI: 10.23939/chcht11.02.188
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Activation and Sorption Ability of Rare Cross-Linked Networks in Intergel System Based on Polymethacrylic Acid and Poly-4-Vinylpyridine Hydrogels in Relation to Lanthanum Ions

Abstract: Abstract.1 Sorption ability of intergel system polymethacrylic acid hydrogel (gPMAA) -poly-4-vinylpyridine hydrogel (gP4VP) in relation to lanthanum ions is studied. Hydrogels mutual activation in an aqueous medium, particularly dependencies of swelling coefficient, specific electric conductivity and pH of water solutions are studied. Maximum activation of hydrogels occurs at gPMAA:gP4VP molar ratio 3:3. Maximum total binding degree of polymer chain in the intergel system is observed at the ratio gPMAA:gP4VP =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…The remote interaction phenomenon [ 29 , 30 , 31 , 32 ] provides a transition of initial macromolecular structures (in the work, ion-exchange resins Amberlite IR120 and AB-17-8) into highly ionized state due to their mutual activation. Activation is a transfer of functional groups from less reactive state to more reactive state and appearance of high ionization and relaxation areas of initial ion exchangers in interpolymer pairs.…”
Section: Resultsmentioning
confidence: 99%
“…The remote interaction phenomenon [ 29 , 30 , 31 , 32 ] provides a transition of initial macromolecular structures (in the work, ion-exchange resins Amberlite IR120 and AB-17-8) into highly ionized state due to their mutual activation. Activation is a transfer of functional groups from less reactive state to more reactive state and appearance of high ionization and relaxation areas of initial ion exchangers in interpolymer pairs.…”
Section: Resultsmentioning
confidence: 99%
“…As a result of extensive studies of the rare-earth metals sorption by interpolymer systems consisting of crosslinked polyelectrolytes that undergo a remote interaction, the following advantages of new sorption methods were established [ 46 , 47 ]: Possibility of development of selective sorbents (or sorption systems) for selective sorption of aimed metal ion; Possibility of developing several selective sorbents for sorption of different metals ions on the basis of one interpolymer system; Possibility of application of rather cheap industrial ion-exchangers for creation of interpolymer systems for further sorption of aimed metals ions; Remote interaction provides the transition of each initial component into highly ionized state in interpolymer systems. Each ionized (activated) ion-exchanger can be used as an independent sorbent, which have high sorption properties.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of extensive studies of the rare-earth metals sorption by interpolymer systems consisting of crosslinked polyelectrolytes that undergo a remote interaction, the following advantages of new sorption methods were established [46,47]:…”
Section: Introductionmentioning
confidence: 99%
“…Based on elements such as erbium, neodymium, yttrium, samarium alloys with recordable magnetic properties (high magnetizing and coercive forces) are produced to create permanent magnets of enormous power in comparison with simple ferroalloys [5]. Previous studies [6][7][8][9] have shown that mutual activation of polymer hydrogels leads to significant changes in their conformational and electrochemical properties. Remote interaction is carried out by rapid hydration, ionization, dissociation, association and slow change in the conformational state of inter-node links.…”
mentioning
confidence: 99%
“…Interactions between different types of hydrogels are much less investigated than hydrogels themselves; one can find only individual reports on this research [9,13]. Besides, cited articles [9,13] are devoted to contact interactions of hydrogels. Now we report about sufficiently new phenomena, which demonstrate possibility of electrochemical interactions between samples placed at quite long distance from each other.…”
mentioning
confidence: 99%